OVERVIEW OF ACEH TUNA EXPORT COMMODITY: POLICY PAPER - Hasfiandi, Hasfiandi (LPPM Universitas Malikussaleh, 2024)
This study is part of a policy paper that aims to provide an overview of tuna exports in Aceh. It will examine the competitiveness of fresh, chilled, or frozen tuna commodities and the impact of their export value on the GDP of the fisheries sub-sector in Aceh. The findings will propose strategies for the development and management of tuna exports in Aceh. The study found that the competitiveness of Aceh's fresh, chilled, or frozen tuna commodities is low, with an RCA value of less than 1. Additionally, an increase in tuna export value did not lead to an increase in the GDP of Aceh's fisheries sub-sector. Strategies suggested for developing tuna exports in Aceh include improving logistics processes and cold chain systems at ports, enhancing the potential of processed tuna products like canned tuna and tuna loin, developing medium to large-scale Industrial Processing Units for canned and loin tuna, raising quality standards through regular audits and inspections of local producers implementing HACCP, optimizing the use of fiscal incentives for exporters to help cover the cost of rising export cargo rates, strengthening partnerships with start-ups for trading missions of tuna in the global market at more competitive prices, and enhancing and developing the branding of fresh, frozen, chilled, and processed tuna products through joint councils and chambers of commerce of tuna importing countries.